Knowledge, attitudes, and practices on denture maintenance of walk-in removable denture-wearing patients of the University of the Philippines Manila College of Dentistry on the third shift of second semester A.Y. 2017-2018 - De Leon, Vance Lenin B.; Delos Santos, Anna Nikole G.; Jumao-as, Czarina Mikaela C.; Mutia, Jessa Carmela M.
Introduction: Edentulism has a high prevalence rate in the Philippines. Nine million out of 100 million Filipinos are denture wearers. However, there is no published standard protocol and baseline data regarding denture maintenance of removable denture-wearing patients in the Philippines. As a result, there are varying methods of denture maintenance practiced that may be detrimental to the oral health of the patients and to the integrity of the dentures.